2002
DOI: 10.1007/s100380200004
|View full text |Cite
|
Sign up to set email alerts
|

Nonaka myopathy is caused by mutations in the UDP-N-acetylglucosamine-2-epimerase/N-acetylmannosamine kinase gene (GNE)

Abstract: This is the first report on mutations of the UDP-N-acetylglucosamine-2-epimerase/N-acetylmannosamine kinase gene (GNE) in Nonaka myopathy or distal myopathy with rimmed vacuoles (OMIM 605820), an autosomal recessive neuromuscular disorder. Sequence and haplotype analyses of GNE in two siblings with Nonaka myopathy from a Japanese family revealed that both patients were compound heterozygotes for a CAET transition (A460V) in exon 8 and a GAEC transition (V572L) in exon 10. Their parents and a normal elder broth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 12 publications
0
38
0
1
Order By: Relevance
“…Briefly, 2 l of total RNA (1 ϫ 10 6 cell equivalents) from CHO or Lec3 cells were mixed with 1 l of 500 g/ml oligo dT [12][13][14][15][16][17][18] primer, 1 l of 10 mM dNTP, and 8 l of water and incubated at 65°C for 5 min. After cooling on ice, 4 l of 5ϫ first strand buffer, 4 l of 0.1 M dithiothreitol, and 1 l of RNA OUT were mixed and incubated at 42°C for 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, 2 l of total RNA (1 ϫ 10 6 cell equivalents) from CHO or Lec3 cells were mixed with 1 l of 500 g/ml oligo dT [12][13][14][15][16][17][18] primer, 1 l of 10 mM dNTP, and 8 l of water and incubated at 65°C for 5 min. After cooling on ice, 4 l of 5ϫ first strand buffer, 4 l of 0.1 M dithiothreitol, and 1 l of RNA OUT were mixed and incubated at 42°C for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, Lec3 CHO mutants are well suited for fundamental studies of mutations that alter UDP-GlcNAc 2-epimerase activity including human GNE mutations that cause sialuria and the myopathic disorders, HIBM and Nonaka myopathy (13,14,44 …”
Section: Lec3 Cho Glycosylation Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human CPA4 gene is located on chromosome 7q32, which is a region in the genome that might contain genes for prostate cancer aggressiveness (10). In addition, the CPA4 gene was found to be maternally imprinted in a tissue-specific manner (11,12). Furthermore, imprinting in adult benign hypertrophic prostate tissue suggests that mutations or aberrant imprinting in CPA4 may be related to prostate cancer aggressiveness (12).…”
mentioning
confidence: 99%
“…In addition, the CPA4 gene was found to be maternally imprinted in a tissue-specific manner (11,12). Furthermore, imprinting in adult benign hypertrophic prostate tissue suggests that mutations or aberrant imprinting in CPA4 may be related to prostate cancer aggressiveness (12). Ross et al (13) studied the association of single-nucleotide polymorphisms on the CPA4 gene and its relation to prostate cancer and found that the nonsynonymous coding single-nucleotide polymorphism (G303C) rs2171492 was associated with an increased risk of aggressive disease in younger men.…”
mentioning
confidence: 99%